Total lactic acid bacteria, phenolic compounds and antioxidant activities of pineapple waste and Indigofera zollingeriana leaves by liquid fermentation - Rizki Palupi; Marieska Verawaty; Fitri Nova Liya Lubis; Nova Oktarinah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
This study aims to determine the best combination of pineapple waste liquid fermentation and Indigofera zollingeriana leaves, which produces the highest amount of lactic acid bacteria, the highest vitamin C content, and total phenols, and the best antioxidant from the combination of the fermentation results. The resulting fermentation product will be used as a natural feed additive in poultry rations. This research was conducted with an experimental method using a Completely Randomized Design (CRD), which consisted of five preparations and four replications. The treatments were combination of pineapple waste and Indigofera zollingeriana leaves: P1 (100% pineapple waste), P2 (98% pineapple waste and 2% Indigofera zollingeriana leaves), P3 (96% pineapple waste and 4% Indigofera zollingeriana leaves), P4 (94% pineapple waste and 6% Indigofera zollingeriana leaves) and P5 (92% pineapple waste and 8% Indigofera zollingeriana leaves). Substrate from each combination of pineapple waste and leaves of Indigofera zollingeriana was fermented with the contribution of 10% of lactic acid bacteria obtained from commercial yogurt and incubated for 72 hours. The parameters in this study consisted of total lactic acid (Lactobacillus bulgarius), the concentration of vitamin C, total phenols, and antioxidant activity. The results showed that the combination of pineapple waste and Indigofera zollingeriana leaves proved significantly (P <0.05) to total lactic acid bacteria (Lactobacillus bulgarius), vitamin C concentration, total phenols and antioxidant activity of the fermented liquid (supernatant) products. In conclusion, the combination of 92% pineapple waste and 8% leaves of Indigofera zollingeriana had the highest total bacterial contribution, produced the highest vitamin C and phenolic compounds, and increased antioxidants.